Home Office Expenditure: A critical analysis of the applicable law governing the deductibility of home workspace expenses incurred by persons in employment - given the shift to working from home - Paruk, Ziyaad (Department of Finance and Tax, 2023)
The applicable law governing the income tax deductibility of home workspace expenses incurred by persons in employment has remained contentious and inconclusive. This has been heightened given the accelerated shift toward employees working from home in recent years. It is therefore necessary for there to be research conducted in resolving this heightened contention, with potential legislative amendments being recommended to National Treasury, who have acknowledged that the applicable law needs to be updated. An exposition of the applicable law over the last fifty years is provided, which includes historical analyses and the general mechanics of the law. More complex matters relating to the interpretation of the applicable law are then highlighted and analysed in light of the applicable principles of fiscal statutory interpretation (mainly using the landmark Endumeni approach). The South African Revenue Service (‘SARS') has attempted to update the existing Interpretation Note (‘IN') dealing with home workspace expenditure, for which they released two drafts, both in 2021; and finalised such IN in 2022. Although SARS' interpretations are determined to not be authoritative in terms of the law, their interpretations are analysed in terms of the applicable law to identify and analyse inconclusive matters. These matters relate to the types of home workspace expenses that are tax deductible, and the ‘tests' under section 23(b). Some of the key findings in this regard are that the legislation does not require a separate-room home workspace, and that all of the ‘tests' should be performed for the period which an employee is working from home, even if this period is less than a full year of assessment. Potential legislative amendments are identified, specifically in the short-term, by looking to comparable jurisdictions, namely the United Kingdom and Canada. These jurisdictions offer taxpayers a ‘simplified cost' deduction which is capped to a legislated amount. Legislating a ‘simplified cost' deduction accordingly will provide the fiscus more time to adequately review the applicable law substantially, given the accelerated shift toward employees working from home and heightened contention in this regard.